Noise-Like Pulse Generation Using Polarization Maintaining Mode-Locked Thulium-Doped Fiber Laser With Nonlinear Amplifying Loop Mirror - Maria Michalska; Jacek Swiderski (IEEE Photonics Journal)
We investigate noise-like pulse (NLP) generation in a mode-locked thulium-doped fiber laser with nonlinear amplifying loop mirror (NALM) and different net anomalous dispersions. The all-polarization maintaining (PM) fiber oscillator generates pulse trains with a frequency adjustable in the range of 4.06–20.4 MHz by utilizing different lengths of PM passive fiber in the NALM loop. An NLP with a coherence spike width of 232 fs was generated at 1993.6 nm with a 3-dB spectral width of 32.6 nm when the net cavity dispersion was −0.711 ps2.